Utilizing optical illusions for creative form finding. Issue 3 (2nd July 2020) - Pooripanyakun, Munyaporn; Wodehouse, Andrew
ABSTRACT: Geometrical illusions are an intrinsic part of human perception but largely ignored in product design. This paper analyzes user perception of a functional, ubiquitous object – the plastic bottle – to provide new insights on how geometrical illusions can be harnessed for creative form finding based on the designer's intent. Through the examination of 24 different bottles, a range of characteristics and properties are classified. A subset of five representative bottles are then used to explore user perceptions of form, relating these to geometrical design features. The main findings, based on observational tests and user feedback, suggest an overestimation of volumes in bottles that are taller, have wider shoulder angles, or have less occluded patterns. Furthermore, a number of prevalent features are considered in relation to optical illusions which can affect perception. Using these findings, design strategies and guidelines are suggested for creative form development and the utilization of geometrical illusions more widely.